MANDIBULAR SINGLE COMPLETE DENTURE INSERTION: A RETROSPECTIVE STUDY - Aafreen M, Maajida; V, Ashok; Gurunathan, Deepa (International Journal of Psychosocial Rehabilitation, 2020)
Aim: The aim of the study is to evaluate the number of mandibular single complete dentures given as a retrospective study of 1 year.Materials and methods: The data was collected between a time period of June 2019 to March 2020 and included a sample size of 30 participants. The findings were tabulated in Excel sheets. The data analysis was done using SPSS software, and the output was obtained in the form of pie charts and graphs.Results: The total number of mandibular single complete dentures given was found to be 75.9%. The most common gender showed male compared to female, and based on the patients age, the most common age included 45 to 50 years of age.Conclusion: Within the limits of the given study, the mandibular single complete denture given was high and more prevalent in males with an age group of 45 to 50 years of age.